Among Giants: The Military Bases’ Impacts of Great Power Competition on Djibouti’s National Security - Silaen, Christo Ariel Mario; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (Darul Yasin Al Sys, 2025)
This study addresses the limited research on the implications of great power competition for small states, with a particular focus on Djibouti’s national security, political autonomy, and economic stability. Despite its strategic location and geopolitical significance, Djibouti remains underexamined in the context of rising global military rivalries. The study investigates how the presence of multiple foreign military bases affects Djibouti’s internal and external security dynamics. Employing a qualitative case study approach, data were drawn from official reports, scholarly literature, and strategic analyses, and examined using thematic content analysis to identify key patterns and trade-offs. Findings indicate that while foreign military bases contribute to national security through deterrence and provide economic gains via lease revenues and infrastructure development, these benefits are unequally distributed and come at the cost of growing dependencies that may limit Djibouti’s foreign policy autonomy. The study concludes that Djibouti strategically adopts an omnidirectional hedging approach, maintaining balanced relations with competing powers to preserve its sovereignty and regional relevance. The research contributes to theoretical discourse on small-state strategies in international relations and offers practical policy recommendations for managing foreign military engagements while safeguarding national interests. It also highlights avenues for future research on the broader socio-economic and political implications of foreign base-hosting in strategically located microstates.